Projeto de extensão núcleo de cidadania ativa da Unesp Franca - Gaspardo, Murilo [UNESP]; Oliveira, Adolfo Raphael Silva Mariano de [UNESP]; Ramos, Cauê Andrade [UNESP]; Marchioni, Artur [UNESP]; Silva, Otávio Augusto Mantovani [UNESP]; Ferreira, Ingrid Juliane dos Santos [UNESP]; Branco, Carolina Nishimura Bueno Castelo [UNESP]; Bonfim, Frederico Henrique Ramos Cardozo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The project on screen aims to introduce the activities of the Extension Project “Active Citizienship Center of Unesp/Franca”. Focusing on the first axis of participation, there is noticed the correspondence of the group activities and objectives with the theme of this axis. On this context, the public policies take place as affirmative acts that assure social rights, incontestable and fundamental rights that lead to the effective social participation on the government decisions and consequent consolidation of the democracy and human rights. Keeping this context, the Social Control of the Public Policies emerges as an emancipatory tool that assure the popular participation on government decisions against the corruption of agents that could destitute the public policies from its vocation, turning it in empty government acts. The Center has, therefore, an incontestable compromise with the democracy and with the population, a compromise that will be evident on this project through the highlight of the group objectives, methods and results on the academic and social field.

O projeto em tela visa apresentar o Projeto de Extensão “Núcleo de Cidadania Ativa – Unesp/Franca”. Focando-se no eixo de participação número 1, percebe-se estreita pertinência das atividades e objetivos do grupo com todas as temáticas dispostas no eixo. Nesse contexto, as políticas públicas se inserem como medidas afirmativas e asseguradoras de direitos sociais, direitos estes fundamentais e incontestáveis para a efetiva participação social nas decisões governamentais e consequente consolidação da democracia e dos direitos humanos. Sob este aspecto, o Controle Social das Políticas Públicas surge como ferramenta emancipatória e garantidora de participação popular nas gestões e contra o emparelhamento e cooptação de agentes que possam vir a destituir as políticas públicas de sua vocação, transformando-as em meras ações governamentais vazias. O Núcleo tem, portanto, um compromisso inalienável com a democracia e com o povo, compromisso este que será evidente no projeto através do destaque de seus objetivos, métodos e resultados nos campos acadêmicos e sociais.
Keywords: Active citizenship; Human rights; Social control of the public policies; Cidadania ativa; Direitos humanos; Controle social das políticas públicas